Pengaruh Search Engine Optimization, Integrated Marketing Communication, Perceived Value, dan Tricomponent Attitude Model Terhadap Keputusan Pembelian: Studi pada Konsumen Produk Laptop Lenovo di Komunitas Facebook Lenovo Indonesia - Alfiatur Rohmania; Amma Fazizah; Any Urwatul Wusko (MES Management Journal, 2025)
This research was conducted to determine the influence of search engine optimization, integrated marketing communication, perceived value, and the tricomponent attitude model on purchasing decisions for Lenovo laptop products. This research was conducted on the Lenovo Indonesia Facebook community. This type of research uses descriptive research with a quantitative approach, with questionnaires distributed as a data collection technique. The sampling method used purposive sampling, namely a technique with the aim of conducting research, the sample used was 100 respondents through distributing questionnaires. The data analysis method used in this research is multiple linear regression analysis, and the data processing used is statistical analysis in the form of SPSS 25.0. Based on the results of this research, it can be seen that search engine optimization has a positive and significant effect on purchasing decisions, integrated marketing communication has a positive and significant effect on purchasing decisions, perceived value has a positive and significant effect on purchasing decisions, and the tricomponent attitude model has a positive and significant effect. significant impact on purchasing decisions, and simultaneously search engine optimization, integrated marketing communication, perceived value, and tricomponent attitude model influence purchasing decisions in the Lenovo Indonesia Facebook community.